Uterine artery Doppler in singleton pregnancies conceived after in‐vitro fertilization or intracytoplasmic sperm injection with fresh vs frozen blastocyst transfer: longitudinal cohort study. (11th September 2020) - Cavoretto, P. I.; Farina, A.; Gaeta, G.; Sigismondi, C.; Spinillo, S.; Casiero, D.; Pozzoni, M.; Vigano, P.; Papaleo, E.; Candiani, M.
ABSTRACT: Objective: Pregnancies conceived by frozen blastocyst transfer (FBT) have higher gestational age and weight at birth as compared to those derived by fresh blastocyst transfer. The aim of this study was to evaluate uterine artery pulsatility index (UtA‐PI) in pregnancies conceived by in‐vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) techniques using fresh vs cryopreserved blastocysts. Methods: This was a prospective longitudinal study of viable singleton IVF/ICSI pregnancies conceived after FBT or fresh blastocyst transfer, that underwent serial ultrasound assessment at San Raffaele Hospital, Milan, Italy at 7–37 gestational weeks. We excluded pregnancies conceived using other assisted reproductive techniques such as egg donation, twin gestation, pregnancy with abnormality and those resulting in miscarriage. Pregnant women underwent ultrasound assessment at 7–10, 11–14, 18–25 and 26–37 weeks' gestation. Mean UtA‐PI was measured using Doppler ultrasound according to The Fetal Medicine Foundation criteria. Pregnancy outcomes were recorded. The primary outcome was mean UtA‐PI measurement and secondary outcomes were gestational age at birth, birth weight and fetal and maternal complications, including small‐for‐gestational age (SGA), pre‐eclampsia and large‐for‐gestational age. UtA‐PI values were made Gaussian after log10 transformation. Analysis of repeated measures using a multilevel linear mixed model (fixed effects and random effects) was performed. The possible effect of other covariates on UtA‐PI Doppler values, including body mass index, SGA and pre‐eclampsia, was also evaluated. Results: A total of 367 IVF/ICSI cycles, comprising 164 with fresh blastocyst transfer and 203 with FBT, were included and a total of 625 observations (median, 2.5 (range, 1–4)) were collected and analyzed. The FBT group had on average 14% lower UtA‐PI compared with the fresh‐blastocyst‐transfer group. In pregnancies with SGA fetuses, UtA‐PI was 18% higher compared to pregnancies without, irrespective of the study group. Pregnancies that underwent fresh blastocyst transfer had significantly lower birth‐weight centile (43.4 ± 23.3 vs 50.0 ± 23.1; P = 0.007) and a higher rate of SGA (7.9% vs 2.0%; P = 0.008) compared to those that underwent FBT. No significant differences were found between the two groups with respect to gestational age at birth and rates of preterm birth, pre‐eclampsia, gestational diabetes mellitus and large‐for‐gestational age. Conclusion: UtA‐PI and the proportion of SGA are lower in IVF/ICSI pregnancies conceived after FBT as compared to fresh blastocyst transfer. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.